Trends of Negotiated Targeted Anticancer Medicines Use in China: An Interrupted Time Series Analysis - Cong Huang; Carolina Ung; Haishaerjiang Wushouer; Lin Bai; Xinyi Li; Xiaodong Guan; Luwen Shi (International Journal of Health Policy and Management, 2022)
Background  In order to relieve the financial burden of the patients in China, the Ministry of Health (MoH) conducted the first national price negotiation and successfully negotiated three expensive medicines including 2 targeted anticancer medicines (TAMs), icotinib and gefitinib. However, little evidence was available to demonstrate the impact of the national negotiation on TAMs use. The purpose of the study is to evaluate the implementation of the national price negotiation policy in China on TAMs use. Methods  We used interrupted time series (ITS) design to examine the changes in the daily cost, the monthly hospital purchasing volume and spending of icotinib and gefitinib with pharmaceutical procurement data from 594 tertiary hospitals in 29 provinces of mainland China between January 2015 and July 2017. The period between May and July 2016 was applied to assess the impact of policy.Results  The daily cost of icotinib and gefitinib decreased by 50.08% (P < .001) and 53.89% (P < .001) 12 months after the national negotiation, respectively. In terms of volume, the negotiation was associated with increases in the trend of the monthly hospital purchasing volume of icotinib and gefitinib by 4.87 thousand defined daily doses (DDDs) (P < .001) and 6.89 thousand DDDs (P < .001). However, the monthly hospital purchasing spending of icotinib and gefitinib decreased rapidly by US$0.51 million (P < .010) and US$0.82 million (P < .050) following policy implementation, respectively. Conclusion  The first national negotiation had successfully cut off the price of two negotiated TAMs and promoted TAMs use in China. In the future, government should conduct further price negotiations and include more medicines with clinical benefits into reimbursement schemes to alleviate patients’ financial burden and promote their access to essential treatment.